To improve Africa’s soil health and plant nutrition, empower women farmers - Ringler, Claudia; Masso, Cargele (International Food Policy Research Institute, 2024)
Healthy soils play a critical role in supporting agricultural productivity, climate change mitigation and resilience, and a range of ecosystem services. Up to 65% of Africa’s productive land is estimated to be degraded, and far too many smallholder farmers must eke out a living on degraded and nutrient depleted soils. While many technical options for soil improvement or restoration exist, a large number of them remain “on the shelf” or do not see widespread use due to sociocultural, institutional, economic, and policy barriers that stand in the way of their uptake at scale.